Treatment of depression with a combination of mirtazapine and venlafaxine - a literature review - Szwedkowicz, Agata; Miszuda, Sławomir; Trojan, Sara; Fussek-Styga, Urszula; Błaszczyk, Agnieszka; Kwieciński, Jakub; Basiaga, Bartosz; Bednarz, Krzysztof; Leśniak, Marek; Heluszka, Jakub (Quality in Sport, 2023)
Clinical depression is a psychiatric disorder characterized by symptoms such as loss of interest and pleasure from typically enjoyable activities (anhedonia), pervasive low mood, and diminished energy leading to excessive fatigue and lower activity which have been present in a patient for at least two weeks. Available therapies consist primarily of pharmacological intervention. Indeed, some groups of medications such as SSRIs, SNRIs, TCA’s and tetracyclic antidepressants have been used to treat depression for decades, frequently in combinations. An example of such a combination is “California Rocket Fuel” composed of venlafaxine and mirtazapine Objective: To review the current literature on the efficacy of the combination of venlafaxine and mirtazapine in treating clinical depression both in drug-resistant depression and as a first-line option. To explore the risks and benefits of this choice of therapy and discuss its potential mechanism of action. Methods: Literature review of Pubmed, Google Scholar, Science Direct, and available medical textbooks. Conclusions: Treatment with venlafaxine and mirtazapine is safe, especially for drug-resistant depression. It is worth considering adding venlafaxine to already ongoing pharmacotherapy with mirtazapine when the patient experiences sleepiness and the symptoms of depression have not been sufficiently reduced. Augmenting venlafaxine treatment with mirtazapine also seems necessary when the patient complains of insomnia. One may consider implementing such therapy as a first-line treatment in patients who suffer from depression for a long time and experience insomnia in its course.